Phytoplasma diseases on fruits in Hungary - Süle, Sándor (Acta Agraria Debreceniensis, 2014)
In the last twenty years, three phytoplasma diseases were identified in Hungary, viz. European Stone Fruit Yellows (ESFY) (caused by Candidatus Phytoplasma prunorum), pear decline (caused by Candidatus Phytoplasma pyri), and apple proliferation (caused by Candidatus Phytoplasma mali). Candidatus Phytoplasma prunorum was isolated from apricot, peach, plum and japanese plum. Cacopsylla pruni the vector of ESFY was also isolated and identified. Infection of Candidatus Phytoplasma pyri was diagnosed from pear and Candidatus Phytoplasma mali was found on apple and pear. The three phytoplasmas cause different damages on their host plants. The most economically important phytoplasma disease is the ESFY. It seriously impairs apricot and japanase plum trees. After infection of apricots and japanese plums show yellowing and defoliation, and within a few years die in apoplexy-like symptoms. The disease on japanese plum is so severe that this fruit practically can not be cultivated in Hungary. Pear decline is the most serious problem especially in intensive pear plantations. The vector Cacopsylla pyri, C. pyrisuga and C. pyricola can be found in almost all pear orchards. Because of the regular presence of psyllids in intensive pear orchards the insecticide control is necessary. Apple proliferation is not an important disease in Hungary. All of our isolations of ’Candidatus Phytoplasma mali’ occured in organic orchards and record was not available in Hungary lately.